Reflexive and Intentional Saccadic Eye Movements in Migraineurs - Filippopulos, Filipp M.; Goeschy, Christine; Schoeberl, Florian; Eren, Ozan E.; Straube, Andreas; Eggert, Thomas (Frontiers in Neurology, 2021)
Background: Migraine has been postulated to lead to structural and functional changes of different cortical and subcortical areas, including the frontal lobe, the brainstem and cerebellum. The (sub )clinical impact of these changes is a matter of debate. The spectrum of possible clinical differences include domains such as cognition but also coordination. The present study investigated the oculomotor performance of patients with migraine with and without aura compared to control subjects without migraine in reflexive saccades, but also in intentional saccades, which involve cerebellar as well as cortical networks. Methods: In 18 patients with migraine with aura and 21 patients with migraine without aura saccadic eye movements were recorded in two reflexive (gap, overlap) and two intentional (anti, memory) paradigms and compared to 25 controls without migraine. Results: The main finding of the study was an increase of saccade latency in patients with and without aura compared to the control group solely in the anti-task. No deficits were found in the execution of reflexive saccades. Conclusions: Our results suggest a specific deficit in the generation of correct anti-saccades, such as vector inversion. Such processes are considered to need cortical networks to be executed correctly. The parietal cortex has been suggested to be involved in vector inversion processes but is not commonly described to be altered in migraine patients. It could be discussed that the cerebellum, which is recently thought to be involved in the pathophysiology of migraine, might be involved in distinct processes such as spatial re-mapping through known interconnections with parietal and frontal cortical areas.